Weaknesses in the Reporting of Cross-sectional Studies in Accordance with the STROBE Report (The Case of Congenital Anomaly among Infants in Iran): A Review Article - Morvarid IRANI; Maryam HASSANZADEH BASHTIAN; Talat KHADIVZADEH; Hosein EBRAHIMIPOUR; Seyyed Mohsen ASGHARI NEKAH (Tehran University of Medical Sciences, 2018)
Background: The inadequate reporting of cross-sectional studies, as in the case of the prevalence of Congenital Anomaly, could cause challenges in the synthesis of new evidence and make possible mistakes in the creation of public policies. This study was conducted to critically appraise the quality of the articles involving congenital anomaly prevalence in Iranian infants with the STROBE recommendations. Methods: We performed a thorough literature search using the words "congenital anomaly" "birth defect" and "Iran" in MEDLINE/PubMed, Scopus, SID, Elmnet, Magiran, IranDoc, Iranmedex, and Google Scholar until Aug 2017. In this critical appraisal we focused on cross-sectional studies that reported the prevalence of congenital anomaly in Iranian infants. Data were analyzed using the STROBE score per item and recommendation. Results: The results of 17 selected articles on Congenital Anomaly prevalence showed that the overall accordance of the cross-sectional study reports with STROBE recommendations was about 63%. All articles met the recommendations associated with the report of the study's rationale, objectives, setting, key results and provision of summary measures. Methods and results were the weakest part of the articles, in which recommendations associated with the participant flowchart and missing data analysis were not reported. The recommendations with the lowest scores were those related to the sensitivity analysis (6%, n=1/17), bias (6%, n=1/17), and funding (41%, n=7/17). Conclusion: Cross-sectional studies about the prevalence of congenital anomaly in Iranian infants have an insufficient reporting on the methods and results parts. We recognized a clear need to increase the quality of such studies.